Postsynthesis Treatment Influence on Hydrogen Sorption Properties of Carbon Nanotubes - Obolensky, Michail; Basteev, Andrew; Beletsky, Vladimir; Kravchenko, Andrew; Petrusenko, Yuri; Borysenko, Valeriy; Lavrynenko, Sergey; Kravchenko, Oleg; Suvorova, Irina; Golovanevskiy, Vladimir; Bazyma, Leonid (IntechOpen, 2012)
None